Developing and testing a cost data collection instrument for noncommunicable disease registry planning. (December 2016) - Subramanian, Sujha; Tangka, Florence; Edwards, Patrick; Hoover, Sonja; Cole-Beebe, Maggie
Highlights: We created a costing tool and pilot tested with 11 registries in 5 countries. Registries were able to provide high-quality data using the tool. Our analysis revealed several factors that impact the cost of registry operations. Abstract: Background: This article reports on the methods and framework we have developed to guide economic evaluation of noncommunicable disease registries. Methods: We developed a cost data collection instrument, the Centers for Disease Control and Prevention's (CDC's) International Registry Costing Tool ( IntRegCosting Tool), based on established economics methods We performed in-depth case studies, site visit interviews, and pilot testing in 11 registries from multiple countries including India, Kenya, Uganda, Colombia, and Barbados to assess the overall quality of the data collected from cancer and cardiovascular registries. Results: Overall, the registries were able to use the IntRegCosting Tool to assign operating expenditures to specific activities. We verified that registries were able to provide accurate estimation of labor costs, which is the largest expenditure incurred by registries. We also identified several factors that can influence the cost of registry operations, including size of the geographic area served, data collection approach, local cost of living, presence of rural areas, volume of cases, extent of consolidation of records to cases, and continuity of funding. Conclusion: Internal and external registry factors reveal that a single estimate for the cost of registry operations is not feasible; costs will vary on the basis of factors that may be beyond the control of the registries. Some factors, such as data collection approach, can be modified to improve the efficiency of registry operations. These findings will inform both future economic data collection using a web-based tool and cost and cost-effectiveness analyses of registry operations in low- and middle-income countries (LMICs) and other locations with similar characteristics.